Diseño de un sistema de control interno para la sección de cartera e inventarios, aplicado a la asociación de comerciantes de abastos del mercado mayorista dedicada a la comercialización de productos de primera necesidad. Caso : Proveedora J.A. - Ambuludi Gavilanes, Diego Alfredo (2011)
This thesis is the design of an internal control system for section portfolio and inventories, applied to the business association of market supplies wholesaler dedicated to the marketing of staples case: "Provider J. A. ". The preparation of the internal control is designed as support tools audit such as: internal control questionnaires, narratives, flow layout, all based on the five components of internal control, resulting in weaknesses that must be corrected for better Business Administration Araque, Freddy